Annales Sect in Islamic Historical Research - Alvin Noor Sahab Rizal; Vivi Lutfiani (JURNAL INDO-ISLAMIKA, 2020)
There are many things we learn if we know about life landmark, which eventually will be the history of human’s life. Similarly, the Islamic history and Islamic Historiography, which was developed at the same time with Muslim’s development and does not separated from the general development of Islamic civilization. Historical method is the process of critically examining and recording of past recording and old heritage. The data obtained by this process of Past Imaginative reconstruction is known as Historiography. The aim of studying Islamic history is designed to broaden our understanding, to know an incredible fact that may not have been heard by people. By using this thinking framework the historians objectively guided to conduct their research.